2019
DOI: 10.1016/j.ebiom.2019.02.055
|View full text |Cite|
|
Sign up to set email alerts
|

STING-mediated intestinal barrier dysfunction contributes to lethal sepsis

Abstract: Background Gut integrity is compromised in abdominal sepsis with increased cellular apoptosis and altered barrier permeability. Intestinal epithelial cells (IEC) form a physiochemical barrier that separates the intestinal lumen from the host's internal milieu and is strongly involved in the mucosal inflammatory response and immune response. Recent research indicates the involvement of the stimulator of interferons genes (STING) pathway in uncontrolled inflammation and gut mucosal immune response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 32 publications
5
109
0
Order By: Relevance
“…The results of Zeng et al and our group demonstrated that the activation of STING signaling significantly aggravate intestinal pro-inflammatory injury and impairs gut barrier during sepsis [8,9]. We further showed that intraperitoneal injection of mtDNA promoted the induction of inflammatory cytokines via STING signaling [9]. These data identify the crucial yet paradoxical roles of mtDNA-STING pathway in gut barrier maintenance.…”
supporting
confidence: 65%
“…The results of Zeng et al and our group demonstrated that the activation of STING signaling significantly aggravate intestinal pro-inflammatory injury and impairs gut barrier during sepsis [8,9]. We further showed that intraperitoneal injection of mtDNA promoted the induction of inflammatory cytokines via STING signaling [9]. These data identify the crucial yet paradoxical roles of mtDNA-STING pathway in gut barrier maintenance.…”
supporting
confidence: 65%
“…Like other pathways of innate immune responses, the activation of the TMEM173 pathway may be the first line of defense against invading pathogens, including viruses [95][96][97][98]. However, the excessive activation of TMEM173 can produce type I interferon (IFNα and IFNβ) and various cytokines (e.g., IL6 and TNF), which cause a cytokine storm [99][100][101][102][103][104][105]. The excessive activation of TMEM173 also triggers inflammasome activation [106], GSDMD-N-mediated pyroptosis and subsequent lethal immunocoagulation response in experimental septic shock [60].…”
Section: Transmembrane Protein 173mentioning
confidence: 99%
“…To address the complications associated with the hydrophilicity and negative charges of CDNs, cationic and/or encapsulating drug carriers have been exploited to improve the tissue and cell delivery of CDNs, while minimizing systemic toxicity 58, 76. Injection of unformulated “free” STING agonists may lead to rapid dissemination into the blood and subsequently cause systemic cytokine storm that can be harmful 77, 78. In one example, c-di-GMP-incorporated nanoparticles elicited 8.2-fold more antigen-specific IgG titers than the “free” c-di-GMP counterpart at the same dose.…”
Section: Sting-activating Drug Delivery Systems In Cancer Immunothmentioning
confidence: 99%